Quantification of Electron Transfer Rates to a Solid Phase Electron Acceptor through the Stages of Biofilm Formation from Single Cells to Multicellular Communities - McLean, Jeffrey S; Wanger, Greg; Gorby, Yuri A; Wainstein, Martin; McQuaid, Jeff; Ishii, Shun’ ichi; Bretschger, Orianna; Beyenal, Haluk; Nealson, Kenneth H (Environmental science & technology, 2010)
Microbial fuel cell (MFC) technology has enabled new insights into the mechanisms of electron transfer from dissimilatory metal reducing bacteria to a solid phase electron acceptor. Using solid electrodes as electron acceptors enables quantitative real-time measurements of electron transfer rates to these surfaces. We describe here an optically accessible, dual anode, continuous flow MFC that enables real-time microscopic imaging of anode populations as they develop from single attached cells to a mature biofilms. We used this system to characterize how differences in external resistance affect cellular electron transfer rates on a per cell basis and overall biofilm development in Shewanella oneidensis strain MR-1. When a low external resistance (100 Ω) was used, estimates of current per cell reached a maximum of 204 fA/cell (1.3 × 106 e− cell−1 sec−1), while when a higher (1 MΩ) resistance was used, only 75 fA/cell (0.4 × 106 e− cell−1 sec−1) was produced. The 1 MΩ anode biomass consistently developed into a mature thick biofilm with tower morphology (>50 μm thick), whereas only a thin biofilm (<5 μm thick) was observed on the 100 Ω anode. These data suggest a link between the ability of a surface to accept electrons and biofilm structure development.